Uma análise da união estável putativa: elementos configuradores - Soares, Claudinei Marques (Universidade Federal do Tocantins, 2020)
It is certain that society and law are dynamic and complex elements, surrounded by changes, adaptations and transformations at all times and new events. In this step, Family Law has been changing, maximum under the new delineations of Private Law brought by the Federal Constitution of 1988. The traditional concept of family for Brazilian Law, was that formed by parents and children united by a marriage controlled by the State. The 1988 Constitution, in a non-exhaustive list, came and extended this concept, recognizing other family entities (stable union and singleparent family). Given this, it has been that the law ended up protecting all forms of family, not only those constituted by marriage, which indicates an advance in the Brazilian legal order, encouraged by the social reality itself. This reality imposes discussion about “simultaneous families” (in which the person maintains affective relationships with two or more people at the same time), notably, the “putative stable union”. This is not a peaceful matter in doctrine or jurisprudence, but it is a reality that cannot remain in legal limbo. In this scenario, this study presents an analysis of the elements that characterize the “Putative Stable Union”, according to the doctrine and jurisprudence on the subject. As main results, it is seen that the recognition of the mentioned institute is subject of heated discussions. Several Courts around the country assert rights to the partner in concurrent relations. In any case, it has been concluded that the higher courts remain attached to the monogamous issue and most of its members do not recognize the Institute of Putativity. At any rate, it seems a position about to gain new directions within the Federal Supreme Court, even aligning with the new order established by the Constitution of 88.